2015
DOI: 10.1007/s00360-015-0947-z
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive activity and its endocrine correlates in the African lesser bushbaby, Galago moholi

Abstract: Steroid hormones play an important role in female reproductive physiology and behaviour and are often used to monitor important female reproductive events. However, such studies are often attempted on captive populations alone, delivering limited data. One such example is the African lesser bushbaby, Galago moholi, for which contradicting observational data exist between captive and free-ranging populations, while hormonal analyses have only been obtained from a single captive population. To extend and rectify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 57 publications
2
33
0
Order By: Relevance
“…Although the fGCM patterns were highly variable and presumably chronically elevated as a result of the captive setup of our study, no disruption of reproductive function was found in five of the seven captive females. As the stress response and the effect of chronically elevated stress is individual specific (Romero 2002), the suppression of reproductive function could have occurred for two of the seven females, both showing irregularity in terms ovarian hormone cycles (Scheun et al 2016b). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the fGCM patterns were highly variable and presumably chronically elevated as a result of the captive setup of our study, no disruption of reproductive function was found in five of the seven captive females. As the stress response and the effect of chronically elevated stress is individual specific (Romero 2002), the suppression of reproductive function could have occurred for two of the seven females, both showing irregularity in terms ovarian hormone cycles (Scheun et al 2016b). …”
Section: Discussionmentioning
confidence: 99%
“…Male and female G. moholi individuals have separate, but overlapping, home ranges, with frequent interaction occurring among individuals (Bearder & Martin 1979). G. moholi has been described as polygynandrous, with two mating periods per year (May and September; Pullen, Bearder & Dixson 2000;Scheun et al, 2016b). Our study animals comprised seven male and female individuals held in captivity at IPS, as well as 14 males and 12 females from the surrounding wild population of Buffelsdrift Conservancy.…”
Section: Study Animalsmentioning
confidence: 99%
See 3 more Smart Citations